Analisis Dampak dan Pengaruh Perang Salib terhadap Dunia Islam - Rifaldi Ahmad; Ansar Tohe (Al-Kindi, 2026)
The Crusades were one of the most significant events in world history, taking place between 1095 and 1291 AD and involving prolonged conflicts between Christian Europe and the Islamic world. This study aims to analyze the historical background of the Crusades, the factors that triggered the conflicts, and their impacts on both the Islamic world and Europe. The study employed a library research method with a historical approach by examining various sources, including books, scholarly journals, and other relevant historical references. The findings indicate that the Crusades were not solely driven by religious motives, particularly the desire to reclaim Jerusalem as a holy city, but were also influenced by political and economic factors, such as the struggle for power and control over strategic trade routes. The Crusades took place in three major phases: the initial success of the Christian forces, the resurgence of the Muslim forces under the leadership of Nur al-Din Zangi and Salah al-Din al-Ayyubi (Saladin), and the final phase marked by the decline of the Crusader states. The conflict had significant consequences for both civilizations. The Islamic world experienced political, economic, and intellectual decline due to prolonged warfare, while Europe benefited from the transfer of knowledge, the expansion of trade, cultural exchange, and the emergence of the Renaissance, which marked the beginning of the revival of Western civilization.